The importance of memorizing the Noble Qur’an in children's academic achievement and its relationship to the culture of the family and society (Analytical extrapolation study) (Journal of Human Sciences, 2020)
The current study aimed to identify the importance of memorizing the Noble Qur’an in the academic achievement of children, and from here the main question of the study emerges: What is the importance of memorizing the Noble Qur’an in children's academic achievement and its relationship to the culture of the family and society? For the scientific answer to the question posed, this study traced the elements of this topic in terms of the benefits and importance of the Noble Qur’an in developing perceptions and the ability to comprehend and comprehend, and what was done in this field in terms of scientific studies and theories, then it stood at the models and areas of memorizing the Holy Qur’an, after that these arrived The study aims to identify some cultural and social obstacles, some personal and health obstacles, and the most important factors that limit the effectiveness of memorizing the Qur’an for children in society and their lack of academic achievement, and what solutions can be developed for this problem. Based on the inductive analytical approach followed in this study, it has concluded that memorizing the Holy Qur’an was - and still is - an effective element in raising the academic achievement of children in Libyan society, and it has many positive benefits and effects that are narrow at the family level and broad at the national level. As for the obstacles that limit the effectiveness of memorizing the Qur’an for children, they can be solved by starting from narrow to broad solutions, that is, solving the obstacles that are specific to children, and then the obstacles related to the family, then the school, then society, this, and we hope that this study will be followed by other field studies of the importance of memorization The Noble Qur’an in increasing the educational achievement of children in a narrow and specific context: the family, for example. And then determine the problems related to that framework.